Sepsis - What's new in 2019?. Issue 2 (April 2019) - Nunnally, Mark E.; Patel, Arpit
Abstract : Purpose of review: Sepsis-3 guidelines have implications in a deeper understanding of the biopathology of the disease. Further, the review focuses on timely topics and new literature on fluid resuscitation, the value of steroids in sepsis, and new therapeutic options such as angiotensin II, vitamin C, and thiamine as well as the emerging role of procalcitonin (PCT) in managing antibiotics. Recent findings: Traditional therapies such as type of crystalloid fluid administration and steroid therapy for sepsis are currently under re-evaluation. Angiotensin II is investigated for reversing vasodilatory shock. The role of capillary endothelium leak and cellular metabolism can be affected by vitamin C and thiamine levels. Biomarker level trends, specifically PCT, can aid clinical suspicion of infection. Summary: Sepsis-3 shifts the focus from a noninfectious inflammatory process and an emphasis on a dysregulated host response to infection. Hyperchloremic crystalloid resuscitation is associated with poor clinical outcomes. Steroid administration can reverse shock physiology; however, mortality benefits remain uncertain. Angiotensin II, vitamin C, and thiamine are novel treatment options that need further validation. PCT assays can help discern between infectious and noninfectious inflammation.